Identifikasi Mangrove Di Kawasan Ekowisata Mangrove Gampong Baro, Kecamatan Setia Bakti, Kabupaten Aceh Jaya - Faisal Syahputra; Rizki Ramazan; Suraiya Nazlia; Mukhlis Mukhlis; Agus Naufal (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This research was conducted from December 2019 to March 2020, aimed atknow the ecological conditions, community structures and types of mangrove forest utilization in the mangrove ecotourism area of Gampong Baro, Setia Bakti District, Aceh Jaya Regency. Data collection was carried out through field surveys. This data analysis uses an important value index (IVI) which is a quantitative parameter that can reflect the role and structure of mangrove vegetation in a location. At the mangrove tree level, saplings and seedlings the Rhizophora apiculata had the highest value. Diversity index (H') is strongly influenced by individuals and the number of species. At the tree, sapling and seedlings level showed a moderate species diversity result. Dominance index (D) at the treel, tillers and seedling level can be categorized as moderate dominance and the environmental conditions are quite stable.